2018
DOI: 10.1108/jfc-11-2016-0070
|View full text |Cite
|
Sign up to set email alerts
|

Tax malfeasance of high net-worth individuals in Malaysia: tax audited cases

Abstract: Purpose This paper aims to analyse the profiles of high net-worth individuals (HNWIs) who were caught for tax malfeasance during a tax audit and to examine factors that influence tax malfeasance among HNWIs in Malaysia. Design/methodology/approach This paper examined 235 HNWIs who were involved in tax malfeasance after audited by the Inland Revenue Board Malaysia from year 2009 to 2013. A research model was developed to examine the influence of four independent variables which are tax rate, level of income, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Therefore, the return on asset fraud financial statement allegedly tends to increase this. This analysis is then projected into the future to see the company's ability to generate profits in the future [16].…”
Section: E Financial Targetmentioning
confidence: 99%
“…Therefore, the return on asset fraud financial statement allegedly tends to increase this. This analysis is then projected into the future to see the company's ability to generate profits in the future [16].…”
Section: E Financial Targetmentioning
confidence: 99%
“…Tax Professionals refer to the ones working in the taxation industry to include tax practitioners, tax advisers, tax preparers, tax agents, tax accountants, tax intermediaries and tax lawyers. The dummy variable 1 indicates that companies hired tax professionals or 0 otherwise, consistent with Che Rosli et al (2018). Company Age represents total number of years in business, consistent with Sapiei et al (2014).…”
Section: Model Specifications and Variables Measurementmentioning
confidence: 79%
“…This study anticipates that the longer a company in existence, the more cost obligations a company will incur to stay afloat and thus, a company has to find ways to control its ever-growing cost problems and manipulating the books are seen as a quick solution. This may be inspired by the recent studies conducted in Malaysia by Mohamad et al (2017) and Che Rosli et al (2018), but on individual taxpayers, where they found that the older generation of taxpayers were found to be significantly less compliant than their younger counterparts, because of having more financial obligations and commitments. One of the unique characteristics of SMEs where their operations are usually run by a few family individuals may have led to believe that this would be the similarity between the results of SME and individual taxpayers.…”
Section: Duration Of Company In Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying people or firms with offshore ownership can trigger greater investigations from home country tax authorities (van Hulten, 2012). Given demands by the public and politicians, tax authorities will often focus audit resources on those firms/individuals thought to be hiding income, even if this means hiding it in foreign locations (Che Rosli et al, 2018). Another potential downside of shifting taxes to foreign locations can come in the form of consumer boycotts (Akamah et al, 2018).…”
Section: Taxes and Secrecymentioning
confidence: 99%